PENGARUH KEPERCAYAAN WAJIB PAJAK PADA ACCOUNT REPRESENTATIVE TERHADAP KEPATUHAN WAJIB PAJAK (STUDI PADA KANTOR PELAYANAN PAJAK PERUSAHAAN MASUK BURSA EFEK INDONESIA) - Choiriyah, . (Jurnal Mahasiswa Perpajakan, 2014)
The purpose of this research is to know simultan and partial influence of taxpayer’s trust on account representative toward to tax compliance. Taxpayers trust represented by three variables: ability, benevolence and integrity. The method used in this research is explanatory research method, using a questionnaire as a data tool that distributed directly to 93 respondents. Analysis data in this study using descriptive analysis and multiple linear regression analysis aided by SPPS software version 17. The results of this paper indicated thatability variable, benevolence variable and Integrity variablesimultaneously have a significant effect toward taxpayer compliance but partially only ability and benevolence variable has a significant effect toward tax compliance. So that Account representative required to have ability, benevolence and integrity in order to improve tax compliance. Keywords: trust, ability, benevolence, integrity, account representative, tax compliance